Effect of Exercise Barrier Hop and Jump to Box To Improvement Power Muscle Kampung Jawa Regency Men's Volleyball Club Legs Greater Sumbawa in 2025 - Subakti; Nurdin (Jurnal Pengetahuan dan Pendidikan, 2025)
Ball volleyball is one of the branch a popular sport in Indonesia. Volleyball is also expected capable make it fragrant Name nation and state at the event International. Purpose study This For know There is or whether or not influence exercise barrier hop and jump to box to improvement power muscle legs volleyball club son of Kampung Jawa, Sumbawa Besar Regency in 2025 ”. The sample used totaling 16 people, the data collection method uses method test actions as method the main thing , namely with stage test beginning before do exercise use jump to box and barrier hop (pre-test) and after exercise (post-test). Research test instrument For measuring muscle power legs with the vertical jump test , while method data analysis with use analysis statistics with t- test formula . From the results data analysis where treatment use jump to box there is significant influence where t- count more big from t- table (4.849 > 1.895) so based on In the above analysis , Ho is rejected and Ha is accepted. so conclusion from study This that is there is “ The Effect of Exercise Barrier Hop And Jump To Box To Improvement Power Muscle The Leg of the Men's Volleyball Club of Kampung Jawa, Sumbawa Besar Regency in 2025" . Meanwhile, data analysis where treatment use barrier hop there is significant influence where t- count more big from t- table (5.789 > 1.895) so based on In the above analysis , Ho is rejected and Ha is accepted. so conclusion from study This that is There is Effect of Exercise Barrier Hop And Jump To Box To Improvement Power Muscle The Leg of the Men's Volleyball Club of Kampung Jawa, Sumbawa Besar Regency in 2025